PENINGKATAN PEMAHAMAN MATERI BANGUN DATAR DENGAN MENGGUNAKAN MEDIA KERTAS ORIGAMI PADA SISWA KELAS VI MI DATOK SULAIMAN PUTRA - Mawarni Mawarni (Institut Agama Islam Negeri Palopo, 2019)
This research discusses the improvement of students' understanding of mathematics, especially flat-up material. To find out whether the application of origami paper media in class VI MI Datok Sulaiman can improve students' understanding. This research is classroom action research (CAR) which consists of two cycles, each cycle carried out as much as 2 meetings, with stages of Planning, Implementation, Observation, and Reflection. The results showed that: by applying origami paper media can improve the material understanding of students 'flat wake, Based on the test of student learning outcomes in the sixth grade of MI Datok Sulaiman Putra Palopo which was conducted in two cycles showed that students' learning outcomes increased, from the first cycle the average score the mean is 76 with a percentage of completeness of 71% while the second cycle has an average value of 87 with a percentage of 96% and has met the KKM value of 70.